Implikasi Hukum Pemutusan Sepihak Perjanjian Kerja Sama: Analisis Putusan 351/Pdt.G/2021/PN. Bekasi - SIMANULLANG, ENJELINA; Rosmidah, Rosmidah; Fathni, Indriya (Zaaken: Journal of Civil and Business Law, 2025)
One aspect that is often disputed in the business world is about agreements, especially cooperation agreements. Generally, disputes regarding cooperation agreements arise after one party has committed a breach of contract. In this situation, each party will try to get what is considered their right. The courts play an important role in resolving these disputes. The judicial institution functions as a medium for the Plaintiff and Defendant to convey their arguments, especially in an effort to defend their respective rights. This study aims to explore and understand the legal implications of terminating the agreement through a philosophical, legal, and sociological approach. The method used is a normative legal study that analyzes the conflict of norms between the decision of the panel of judges and the provisions of the Civil Code (KUH Perdata), especially Article 1266 which regulates the terms of termination of the agreement. The results of the analysis show that the unilateral termination carried out by the defendant was in accordance with applicable legal provisions, but left a significant legal impact on the relationship between the parties. This means that aspects of justice, legal certainty, and legal benefits must be considered in a balanced manner in every termination of a cooperation agreement. The article is expected to contribute to the development of civil law in Indonesia and become a reference for further research in the field of contract law.